Slave Life and Slave Law in Colonial Prince Edward Island, 1769-1825 - Whitfield, Harvey; Cahill, Barry (Acadiensis, 2009)
Abstract Prince Edward Island (colonial Saint John’s Island) is unique among slaveholding jurisdictions in what is now Canada both for having enacted in 1781 an embryonic slave code and for doing so before the unanticipated post-war migration of American Loyalists that was responsible for most of the slaves brought there. This is an anomaly that begs for explanation. Placing it in the context of the Loyalist experience of slaves and slaveholders in Atlantic Canada, this article examines the Prince Edward Island case from the perspective of law and slavery in 18th-century Scotland and the Scottish regime on Prince Edward Island.